Strengthening of hot-worked powder steels - Maxim S. Yegorov; Rimma V. Yegorova; Victor N. Pustovoyt (Advanced Engineering Research, 2016)
The work objective is to study the fundamental processes of forming hot-worked powder steels (HWPS) and bonding the particulate material on the existing and newly formed contact surfaces. The role of splicing is particularly great in the process of manufacturing materials under the strained conditions. Evidently, whatever the structure in the amount of the material surrounded by the former powder particle surface, the powder material properties will be determined not by the morphological structural features, but by the splice quality up to a defined level of splicing. Therefore, the study of interparticle splicing in the formation of HWPS is a crucial task of the materials technology. Thus, further processing of hot pressurized powder steels can be offered not only for forming, but to improve their mechanical properties as well.